Sports at the vanguard of labor market policy - Kerry L. Papps (IZA World of Labor, 2020)
Economic theory has many predictions regarding how workers should be paid and how workplaces should be organized. However, economists' attempts to test these in the real world have been hampered by a lack of consistent information about workers' productivity levels. Professional sports offer a potential solution, since the performance of individual sportspeople is easily observed and yet many of the same problems faced by managers in workplaces still apply. In many ways, sportspeople may be less atypical of the modern workforce than farm laborers, doctors, or other groups of workers that are often scrutinized by economists.
Keywords: J24; J71; L22; L83; M12; M52; 330; sports; productivity; teams